Hydroxychloroquine Effects on TLR Signalling: Underexposed but Unneglectable in COVID-19 - Aliede E. in ‘t Veld; Manon A. A. Jansen; Luuk C. A. Ciere; Matthijs Moerland (Journal of Immunology Research)
The main basis for hydroxychloroquine (HCQ) treatment in COVID-19 is the compound’s ability to inhibit viral replication in vitro. HCQ also suppresses immunity, mainly by interference in TLR signalling, but reliable clinical data on the extent and nature of HCQ-induced immunosuppression are lacking. Here, we discuss the mechanistic basis for the use of HCQ against SARS-CoV-2 in a prophylactic setting and in a therapeutic setting, at different stages of the disease. We argue that the clinical effect of prophylactic or therapeutic HCQ treatment in COVID-19 depends on the balance between inhibition of viral replication, immunosuppression, and off-target side effects, and that the outcome is probably dependent on disease stage and disease severity. This is supported by the initial outcomes of the well-designed randomized controlled trials: so far, evidence for a beneficial effect of HCQ treatment for COVID-19 is weak and conflicting.